Freedom of Information and Parliamentary Departments. Issue 1 (March 2014) - Adams, Carolyn
<x xml:space="preserve">Abstract</x> This article examines whether freedom of information (FOI) legislation should apply to those agencies working to support parliaments. In the past, FOI legislation was characterized as a mechanism to allow greater scrutiny of the executive branch by parliament and the community. On this analysis, there was no reason to extend the legislation to the agencies of the legislative branch. But the role of FOI legislation has developed so that it now forms part of a wider integrity framework of government. The need to ensure integrity is a concern for all three branches of government and this article asks whether there are any convincing reasons in principle or practice to exclude the parliamentary departments from the FOI regime.